Mobilidades geográfico-profissionais de duas gerações de agricultores familiares assentados na Amazônia oriental - SARTRE, Xavier Arnauld de (Museu Paraense Emílio Goeldi, 2022)
This article is about the new patterns of migration among farmer families in the eastern Amazon. These patterns were commonly framed as a strategy of social mobility, where moving was a way to acquire land. However, recent studies have shown that migration drivers are evolving because of social modernization and the rise of educational standards. While farmer families’ new strategies are well known, such as investing in education and moving to cities, little attention has been given to their quantification. By examining three “projetos de assentamento” (settlement projects) in the eastern Amazon, we wish to highlight the diversity of strategies that are used, and examine the way they relate to existing geographical and social settings.